2016
DOI: 10.1007/s13277-016-5240-6
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-associated antigen 9 (SPAG9) promotes the survival and tumor growth of triple-negative breast cancer cells

Abstract: Recently, we demonstrated the association of sperm-associated antigen 9 (SPAG9) expression with breast cancer. Among breast cancer, 15 % of the cancers are diagnosed as triple-negative breast cancers (TNBC) based on hormone receptor status and represent an important clinical challenge because of lack of effective available targeted therapy. Therefore, in the present investigation, plasmid-based small hairpin (small hairpin RNA (shRNA)) approach was used to ablate SPAG9 in aggressive breast cancer cell line mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 28 publications
4
29
0
Order By: Relevance
“…p21 is an important regulator of cell proliferation and survival in TNBC cells under various stimulatory pathways . We therefore examined p21 protein levels upon NFIB depletion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…p21 is an important regulator of cell proliferation and survival in TNBC cells under various stimulatory pathways . We therefore examined p21 protein levels upon NFIB depletion.…”
Section: Resultsmentioning
confidence: 99%
“…NFIB-depleted cells were larger and had a flattened shape compared with control cells. Flow cytometry analysis of MDA-MB-435 and HCC1806 showed increased proportions of cells in the S/G2 phases of the cell cycle upon NFIB depletion suggesting a role for NFIB in cell cycle progression p21 is an important regulator of cell proliferation and survival in TNBC cells under various stimulatory pathways [31][32][33]. We therefore examined p21 protein levels upon NFIB depletion.…”
Section: Gene Copy Numbers and Nfib Expression Are Preferentially Elementioning
confidence: 99%
“…SPAG9 protein localization in different cell organelles of ovarian cancer cells was examined using IIF as described previously. 10 Images were captured using Carl Zeiss LSM 510 Meta confocal microscope (Zeiss, Oberkochen, Germany). For co-localization studies antibodies used were: endoplasmic reticulum (Calnexin; Sc70481), mitochondria (MTCO2; ab3298), Golgi bodies (GM130; Sc55591) and nuclear envelope (Lamin a/ c; Sc7292).…”
Section: Spag9 Protein Localization By Indirect Immunofluorescence (Iif)mentioning
confidence: 99%
“…9 Recently, it has been reported that SPAG9 plays an important role in various molecular pathways including cell cycle, apoptosis and epithelial mesenchymal transition (EMT) in triple negative breast cancer. 10 However, till date the involvement of SPAG9 at molecular level in ovarian cancer is not yet explored.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sperm associated antigen 9 (SPAG9) has been shown to be expressed in various cancer types such as epithelial ovarian cancer (EOC-90%) [13], renal cell carcinoma (RCC-88%) [14], colorectal cancer (74%) [15], breast cancer (88%) [16] and cervical cancer (82%) [17]. Studies on SPAG9 also showed that it is associated with cellular proliferation, migration and invasion of cancer cells [18][19][20][21], and is capable of eliciting humoral immune responses in a majority of epithelial ovarian cancers (67%) [13], breast cancers (80%) [16], cervical cancers (80%) [17], renal cell carcinoma (77%) [14], colorectal cancer (74%) [15] and hepatocellular carcinoma [22]. However its antigenicity in invoking a cell mediated immune response has not been studied until now.…”
Section: Introductionmentioning
confidence: 99%